ANALISIS MINAT MAHASISWA MASUK PRODI PJKR UNIVERSITAS MUHAMMADIYAH BANGKA BELITUNG TAHUN 2024/2025 - Oktarina; Erick Prayogo Walton; Pitri Yanti (EDU RESEARCH, 2024)
The problem behind this research is to see how much students are interested in the Physical Education and Recreational Health (PJKR) study program, and the factors that influence student interest in the PJKR study program at the University of Muhammadiyah Bangka Belitung in 2024/2025. The purpose of this study was to find out how much students are interested in entering the Physical Education and Recreational Health (PJKR) study program. This type of research is quantitative descriptive with survey methods for collecting data in the form of material expert sheets, linguists and questionnaires (questionnaires). The subjects in this study were as many as 80 new students entering the Physical Education and Recreational Health study program (PJKR) at the University of Muhammadiyah Bangka Belitung were tested statistically with the SPSS version 25 program. The results showed that the analysis of student interest in the Physical Education and Recreational Health and Recreation Study Program (PJKR) Universitas Muhammadiyah Bangka Belitung in 2024/2025. There are internal factors, namely Motivation with a percentage of 90.52%, Aspirations with a percentage of 88.85%, Desire with a percentage of 89.37%, Family Education with a percentage of 84.53%, Economics with a percentage of 86.56%, School environment with a a percentage of 84.68%, friends with a percentage of 83.12% and teachers with a percentage of 84.89%. And external factors, namely feeling happy with a percentage of 92.18%, interest with a percentage of 87.81%, tendencies with a percentage of 84.68%, activity with a percentage of 86.87. So that things that play a high role from external factors are feelings of pleasure with a percentage of 92.18%.